STUDY OF POROSITY FORMATION OPTIMIZATION IN ALSI9 CU3 ALLOY IN HPDC AND ENHANCEMENT OF BREAK LOAD - Vinod Kumar Verma; Sanjeev Sharma; Sandeep Phogat; Ajay Kumar Mishra; P.B. Sharma (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
In order to examine the impact of porosity on the variability of mechanical characteristics in HPDC Al alloys, we used micro computed tomography to analyze the shape and three-dimensional distribution of porosity in the tensile samples. The experimental findings indicate that the variation in mechanical characteristics of the HPDC AlSi7MgMn alloy is directly linked to the size and overall volume of the pores. The maximum pore size decreases when the alloy undergoes T6 heat treatment and elongates. Additionally, the total volume of porosity decreases as the elongation of the alloy increases. The researchers discovered that a pore size with a diameter of around 1.3mm was associated with an elongation of 6.4%. Upon reaching a size smaller than 0.3mm, the alloy exhibited an increase in elongation, ranging from 9% to 13.5%. When comparing the porosity-free AlSi9 Cu3 alloy samples produced by gravity casting to the HPDC AlSi7MgMn alloy, it can be observed that the latter has similar strength levels and improved elongation, averaging at 11.5%. The elongation, yield strength, and ultimate tensile strength for the AlSi7MgMn alloy are 236.6MPa and 296.0MPa, respectively. This suggests that the amount of porosity is a decisive component in the variability of mechanical properties, and that porosity with a size less than 0.3mm does not have a major negative impact on the mechanical characteristics of the alloy. The increase in elongation in HPDC AlSi9 Cu3 alloy can be attributed to the smaller grain size, with an average value of 10μm, compared to the average value of 500μm in the gravity casting AlSi9 Cu3 alloy. Additionally, the reduction in size and uniform distribution of porosity resulting from the subsequent grain size refinement also contributes to the improvement.